Pendampingan Pengisian dan Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi pada Kantor Pelayanan Pajak (KPP) Pratama Sidoarjo Barat - Whindi Ayu Mayrena; Sakina Nur Hayati; Ifta Takhul Laiya; Kafidin Muzakki (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
E-Filing Service for Individual Taxpayers 1770 S to complete and report their annual SPT. According to Article 1 of Law Number 6 of 2009, the SPT or Announcement Letter is a document that must be applied by Taxpayers to inform the calculation and payment of tax on both tax and non-tax objects, assets and liabilities in accordance with applicable taxation law. regulation. Form 1770 S is intended primarily for simple individual taxpayers who have a gross income of more than Rp. 60 million per year. Before completing and filing the 1770 S Annual Tax Return, taxpayers must provide several documents, including Taxpayer Identification Number (NPWP), Electronic Filing Identification Number (EFIN), and proof of withholding. This Annual SPT reporting technique is carried out online via the DJP website www.djponline.pajak.go.id or via application.